2015
DOI: 10.1007/s10865-015-9627-4
|View full text |Cite
|
Sign up to set email alerts
|

Associations between sleep difficulties and risk factors for cardiovascular disease in veterans and active duty military personnel of the Iraq and Afghanistan conflicts

Abstract: Recent evidence suggests that sleep disturbance may play an important role in the development of cardiovascular disease (CVD). Despite the prevalence of sleep complaints among service members of recent military conflicts, few studies have examined associations between sleep and risk factors for CVD in this population. Symptom checklist items regarding distress about "trouble falling asleep" and "restless/disturbed sleep" were used as proxies for sleep onset and maintenance difficulties to examine these associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 57 publications
0
11
0
3
Order By: Relevance
“…Adolescent sexual assault was a significant predictor of MSA among males but not among females. Sleep Swinkels et al, 2013 Sleep durations of less than 5 hours and greater than 9 hours were each associated with increased odds of current PTSD, MDD, and smoking. Poor sleep quality was also associated with PTSD, panic disorder, MDD, suicidal ideation, and risky drinking. Ulmer et al, 2015 The combination of sleep-onset and sleep-maintenance difficulties wereassociated with risk factors for hypertension and cardiovascular disease, including greater odds of current smoking and psychiatric symptomotology, as well as elevated systolic blood pressure in certain age-by-race interactions. Psychometric properties of measures McDonald et al, 2008; McDonald, Beckham, Morey, & Calhoun, 2009; McDonald et al, 2014 Prior to the emergence of the new DSM-5 PTSD criteria, a four-factor structure of PTSD had emerged in our sample cohort as providing the best fit using the Davidson Trauma Scale (DTS) (McDonald et al, 2008). Early investigations suggested that although a cut score of 40 was originally recommended by the developers of the DTS, in this cohort different cut points may be optimal for different purposes (McDonald et al, 2009; McDonald et al, 2014).…”
Section: Table A1mentioning
confidence: 97%
“…Adolescent sexual assault was a significant predictor of MSA among males but not among females. Sleep Swinkels et al, 2013 Sleep durations of less than 5 hours and greater than 9 hours were each associated with increased odds of current PTSD, MDD, and smoking. Poor sleep quality was also associated with PTSD, panic disorder, MDD, suicidal ideation, and risky drinking. Ulmer et al, 2015 The combination of sleep-onset and sleep-maintenance difficulties wereassociated with risk factors for hypertension and cardiovascular disease, including greater odds of current smoking and psychiatric symptomotology, as well as elevated systolic blood pressure in certain age-by-race interactions. Psychometric properties of measures McDonald et al, 2008; McDonald, Beckham, Morey, & Calhoun, 2009; McDonald et al, 2014 Prior to the emergence of the new DSM-5 PTSD criteria, a four-factor structure of PTSD had emerged in our sample cohort as providing the best fit using the Davidson Trauma Scale (DTS) (McDonald et al, 2008). Early investigations suggested that although a cut score of 40 was originally recommended by the developers of the DTS, in this cohort different cut points may be optimal for different purposes (McDonald et al, 2009; McDonald et al, 2014).…”
Section: Table A1mentioning
confidence: 97%
“…Achieving adequate amounts of restorative sleep is an ongoing problem that is critical for reasons of personal safety, unit performance, and even a matter of national security. Although there are educational resources in place for optimizing sleep in military personnel (e.g., Army Office of the Surgeon General’s Performance Triad (P3) initiative), poor sleep hygiene in the long-term can increase sleep problems co-morbid with physiological and psychological issues that include: cardiovascular disease [1], substance abuse [2], post-traumatic stress disorder (PTSD), and mood disorders [35].…”
Section: Introductionmentioning
confidence: 99%
“…Общая распространенность кардиометаболических ФР ССЗ среди военнослужащих на глобальном уровне с использованием метода метаанализа случайных данных в последних по времени публикациях, для гиперхолестеринемии, гипертриглицеридемии, низкого уровня холестерина липопротеинов низкой плотности и высокого уровня глюкозы в крови натощак составила 21% (17-25), 32% (27-36), 34% (10-57), 24% (16-31), 28% (17-38) и 9% (5)(6)(7)(8)(9)(10)(11)(12), соответственно (в скобках -95% ДИ). Более того, показатели распространенности избыточной массы тела, ожирения, абдоминального ожирения и АГ составляли 35% (31-39), 14% (13)(14)(15)(16), 29% (20-39) и 26% (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34), соответственно [18].…”
Section: особенности фр среди военнослужащихunclassified
“…Согласно данным регистра участников военных действий в Ираке и Афганистане (n=1855), молодые военнослужащие могут иметь относительно высокий риск ССЗ, связанных с нарушениями сна. Показано, что риск ССЗ выше у военнослужащих с умеренными и тяжелыми расстройствами сна и у лиц, имеющих трудности с поддержанием сна, по сравнению с теми, у кого нет проблем со сном или они минимальны, а также среди курящих, лиц, имеющих диагноз посттравматического стрессового расстройства, имеющих клинически значимые симптомы посттравматического стресса, диагноз депрессии и клинически значимые симптомы депрессии [22].…”
Section: роль психосоматического статуса в развитии ссзunclassified